Grid load balancing using enhance ant colony optimization - Ku-Mahamud, Ku Ruhana; Abdul Nasir, Husna Jamal; Mohamed Din, Aniza (2011)
This study presents a new algorithm based on ant colony optimization for load balancing management in grid computing. The concentration is on improving the way ants search the best resources in terms of minimizing the processing time of each job and at the same time balancing the workload on available resources. An enhanced technique is proposed for the pheromone update activities. Single colony of ants is used for searching the best resources to process jobs. The credibility of the proposed algorithm was tested with other load balancing algorithim and results showed that the proposed algorithm was able to balance the load on the resources.